An Integrative Program to Reduce Stigma in Primary Healthcare Workers Toward People With Diagnosis of Severe Mental Disorders: A Protocol for a Randomized Controlled Trial - Grandón, Pamela; Saldivia, Sandra; Vaccari, Pamela; Ramirez-Vielma, Raul; Victoriano, Víctor; Zambrano, Carlos; Ortiz, Camila; Cova, Felix (Frontiers in Psychiatry, 2019)
Background: People with severe mental disorders (SMD) have higher disease and death rates than the general population. Stigma (negative attitudes and perceptions) contributes to an unfair access to health services and a lower quality of assistance in this population. Stigma is translated into negative attitudes, social distance and discrimination towards this social group. For these reasons, healthcare workers are a priority group for anti-stigma interventions. This study aims to assess the effectiveness of a program specifically designed to decrease negative attitudes and social distance and increase inclusive behaviors in healthcare workers towards people with severe mental disorders. Methods: The design corresponds to a randomized clinical trial. A minimum of 210 healthcare workers from 11 primary care centers in the province of Concepción, Chile, will be randomly chosen to receive the program or be part of the control group. There will be a pre, post and four month evaluation of social distance, attitudes, and behaviors of participants towards people with SMD using standardized scales (Social Distance Scale, Scale of clinician attitude towards mental illness adapted from attitudes of clinicians towards mental illness) and self-reports. The intervention program consists of education strategies, direct and indirect contact with people diagnosed with SMD, and skills development. There will be six face-to-face sessions directly with the participants and two additional sessions with the Directors of each healthcare center. The program involves a facilitator who is a health professional and a co-facilitator who is a person diagnosed with SMD. Discussion: This research will evaluate an intervention program especially designed to reduce stigma in healthcare workers towards people with SMD, a topic on which there is little background information, particularly in low and middle income countries. Having interventions with demonstrated effectiveness for this purpose is essential to ensure equity in healthcare service. Ethics and dissemination: This study has been approved by the Ethics and Scientific Committees of the Health Services of Concepción and Talcahuano. Trial Registration: This study was registered under ISRCTN.com (ISRCTN46464036).